SCOPE: SCUBA-2 Continuum Observations of Pre-protostellar Evolution – survey description and compact source catalogue. Issue 2 (26th February 2019) - Eden, D J; Liu, Tie; Kim, Kee-Tae; Juvela, M; Liu, S-Y; Tatematsu, K; Francesco, J. Di; Wang, K; Wu, Y; Thompson, M A; Fuller, G A; Li, Di; et al.
ABSTRACT: We present the first release of the data and compact-source catalogue for the JCMT Large Program SCUBA-2 Continuum Observations of Pre-protostellar Evolution (SCOPE). SCOPE consists of 850 $μ$ m continuum observations of 1235 Planck Galactic Cold Clumps (PGCCs) made with the Submillimetre Common-User Bolometer Array 2 on the James Clerk Maxwell Telescope. These data are at an angular resolution of 14.4 arcsec, significantly improving upon the 353 GHz resolution of Planck at 5 arcmin, and allowing for a catalogue of 3528 compact sources in 558 PGCCs. We find that the detected PGCCs have significant sub-structure, with 61 per cent of detected PGCCs having three or more compact sources, with filamentary structure also prevalent within the sample. A detection rate of 45 per cent is found across the survey, which is 95 per cent complete to Planck column densities of$N_{\rm {H_{2}}}$ > 5 × 10 21 cm −2 . By positionally associating the SCOPE compact sources with young stellar objects, the star formation efficiency, as measured by the ratio of luminosity to mass, in nearby clouds is found to be similar to that in the more distant Galactic Plane, with the column density distributions also indistinguishable from each other.